Calcium transport abnormality in uremic rat brain synaptosomes. - Fraser, C L (1985)
Brain calcium is elevated in patients and laboratory animals with uremia. The significance of this finding is unclear. We evaluated calcium transport in brain of both normal and acutely uremic rats (blood urea nitrogen = 250 mg/dl) by performing studies in synaptosomes from rat brain cerebral cortex. Synaptosomes are vesicular presynaptic nerve endings from brain that contain mitochondria and are metabolically active. Two mechanisms of calcium transport were evaluated using radioactive 45Ca++ as a tracer. Both mechanisms were evaluated in the absence of exogenously administered parathyroid hormone (PTH). We first evaluated Na+-Ca++ exchange in vesicles that were loaded with NaCl in an external media containing 10 microM CaCl2. Both initial rates of calcium transport and equilibrium levels of calcium accumulation in synaptosomes prepared from uremic rats were significantly greater (P less than 0.005) than in normal. To assess calcium efflux, ATP-dependent calcium uptake (1 mM ATP) was studied in inverted plasma membrane vesicles loaded with KCl. In the uremic synaptosomes, a significant increase (P less than 0.005) in ATP-dependent calcium uptake was observed as compared with the normal. These studies show that (a) Calcium accumulation via the Na+-Ca++ exchanger is increased in synaptosomes prepared from uremic rat brain. (b) Calcium influx into inverted plasma membrane vesicles from uremic rats via the ATP-dependent calcium transport mechanism is increased when compared with normal. (c) The increased calcium accumulation in uremia by both Na+-Ca++ exchange and ATP-dependent calcium transport mechanism appears to be a result of increased synaptosomal membrane permeability to calcium. Both these abnormalities of calcium transport in uremia would tend to increase brain extracellular calcium in vivo. The defects observed in uremia do not appear to be readily reversible, and the relationship to PTH is presently unclear. These abnormalities may affect neurotransmission in the uremic state.